A Woman Haunted: How Graphic Biofiction Revises Mary Shelley’s Early Feminist Life - Maria Juko (European Journal of Life Writing)
Biofiction, literature inspired by the life of real people and histories, has become a popular genre. Rarely, however, have graphic biographies been considered in connection to this rapidly emerging (academic) field. To work out these connections, I want to analyse Manuela Santoni and Alessandro di Virgilio's 2021 Mary Shelley (a German translation of the original 2020 Italian text), a biofictional graphic novel about the life of Mary Shelley, while also considering other examples of the genre. I suggest that graphic novels that draw on real life people -in this case, celebrated author and one of the major influences on Gothic literature, Mary Shelley- make use of the graphic medium and create a new version of their subject. Shelley's relationship with her mother, early feminist writer Mary Wollstonecraft, is a prominent topic of reflection for artists, as well as her relationship with her troubled husband Percy Bysshe Shelley, and her most famous creation, Frankenstein's creature. Biofictional graphic novels thus controvert the biographical genre and  revision it instead as a way of reconnecting with the author in a visual way for a new audience regardless of their familiarity with Shelley's biography.